The Life History, Population and Feeding Biology of Two Paddy Field Frogs, Rana Cancrivora GraVenhorst and R. Limnocharis Boie, in Malaysia - Jaafar, Ibrahim (1995)
The life history, population and feeding biology of two species of frogs (R. cancrivora and R. limnocharis) were studied from April 1992 through September 1993 in the rice growing district of Tanjung Karang, Selangor, Malaysia. The results showed that the breeding periods of the two frogs were correlated with the irrigation phase of the rice growing seasons and were not correlated with the rainfall. The frogs were also found to have two breeding peaks annually as opposed to a single peak for the same species in other localities. Comparison of the life history aspects of the two species showed that R. cancrivora females produced more, and larger sized, eggs than R. limnocharis females. This then produced a chain effect whereby R. cancrivora larvae developed faster and metamorphosed at a larger size than those of R. limnocharis, and then continued to grow at a faster rate, attained a larger size and reached sexual maturity earlier. These factors most probably contributed to the observed disparity i n population size between these two frogs wherein R. cancrivora is about six times more numerous than R. limnocharis. The fact that adults of these two species differ in size is also the main reason as to why they can coexist in the same habitat. Different body sizes allow them to ingest different sized prey items, as was discovered by analysis of their diets, thus avoiding competition for food. Survivor ships from eggs to metamorphosis for both species are low but normal for lentic-water breeding amphibians, and they are deemed sufficient to maintain the population levels if human interference can be substantially reduced. Fluctuations in the population structure are mainly due to recruitment, natural mortality and human interference. The most important food items for both species are insects and about 80% of these insects are pests of rice. Hence these frogs are considered very important biological control organisms in the paddy field habitat.